CULTURE SHAPES CHARACTER - Nurhana Amin (Elite : English and Literature Journal, 2015)
Abstract In this article, the writer aimed to find out how the culture shapes character. The library research was used as the design of this study with the sources from personal and online library. The process of collecting the data is in many ways, the first was searching thesis and browsing some literatures. The other sources were books, articles and journals which have the same variable. Collecting and combining some theories was the last step. The result of this research is culture is one of many factors that influence a person's character. Culture affects perception, and perceptions drives behavior. Thus, the culture has a direct impact on our character. Moreover, our environment, which has cultural influences, shapes our character. AbstrakDalam artikel ini penulis bertujuan untuk mengetahui bagaimana budaya membentuk karakter. Penelitian perpustakaan digunakan sebagai desain penelitian ini dengan sumber dari perpustakaan pribadi dan online. Proses pengumpulan data dalam banyak hal, yang pertama mencari tesis dan mecari beberapa literatur. Sumber lainnya adalah buku, artikel dan jurnal yang memiliki variabel yang sama. Mengumpulkan dan menggabungkan beberapa teori adalah langkah terakhir. Hasil dari penelitian ini adalah Budaya adalah salah satu dari banyak faktor yang mempengaruhi karakter seseorang. Budaya mempengaruhi persepsi, dan persepsi mendorong perilaku. Dengan demikian, budaya memiliki dampak langsung pada karakter kita. Selain itu, lingkungan kita, yang memiliki pengaruh budaya, membentuk karakter kita.